1999
DOI: 10.1097/00005072-199903000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Neurons in the Dentate Gyrus in Humans Suffering from Bacterial Meningitis

Abstract: Background: Excitotoxic neuronal injury by action of the glutamate receptors of the N-methyl-d-aspartate (NMDA) subtype have been implicated in the pathogenesis of brain damage as a consequence of bacterial meningitis. The most potent and selective blocker of NMDA receptors containing the NR2B subunit is (R,S)-alpha-(4-hydroxyphenyl)-beta-methyl-4-(phenylmethyl)-1-piperid inepropanol (RO 25-6981). Here we evaluated the effect of RO 25-6981 on hippocampal neuronal apoptosis in an infant rat model of meningitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
132
3
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 189 publications
(153 citation statements)
references
References 0 publications
11
132
3
7
Order By: Relevance
“…The neuronal damage is caused by the strong inflammatory reaction and direct effects of the microorganism 32 . Significant injury during bacterial meningitis arises from mechanisms of neuronal apoptosis, particularly in the hippocampus; in autopsies cases of bacterial meningitis were found apoptosis of neurons in the dentate gyrus 58 . Apoptosis can involve both the caspasedependent and the caspase-independent pathway 59 .…”
Section: Neuronal Damage and Targets For Adjunctive Therapymentioning
confidence: 99%
“…The neuronal damage is caused by the strong inflammatory reaction and direct effects of the microorganism 32 . Significant injury during bacterial meningitis arises from mechanisms of neuronal apoptosis, particularly in the hippocampus; in autopsies cases of bacterial meningitis were found apoptosis of neurons in the dentate gyrus 58 . Apoptosis can involve both the caspasedependent and the caspase-independent pathway 59 .…”
Section: Neuronal Damage and Targets For Adjunctive Therapymentioning
confidence: 99%
“…In the hippocampal DG, the occurrence of neuronal apoptosis has been observed in humans dying from BM and in corresponding animal models [5,27]. Apoptosis almost exclusively affected the SGZ of the DG targeting stem and precursor cells [14][15][16] and thus, may offer the histomorphologically correlate for the , and the neuronal marker MAP2 (C, F) (n ¼ 9).…”
Section: Discussionmentioning
confidence: 99%
“…Brain injury caused by BM prominently affects the hippocampus, a brain region involved in learning and memory function [5,6]. Cells in the hippocampal dentate gyrus (DG) selectively undergo apoptosis, predominantly in the subgranular zone of the DG.…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence points toward an involvement of the hippocampal formation: an increased apoptosis in the dentate gyrus has been found after BM at autopsy. 2 Another study 3 showed bilateral hippocampal volume loss in patients with temporal lobe epilepsy with prior encephalitis or meningitis. In addition to the meningitis itself, the bacteriemia seems to play an important role in the development of apoptosis in bacterial meningitis, as demonstrated in a rat model of bacterial meningitis.…”
mentioning
confidence: 99%